The Effect of Pre-Reading, During Reading, and Post Reading Activities to Monitor Students’ Comprehension in Reading Narrative Text - Nadirah Julia Ulfah Tanjung; Yani Lubis; Ernita Daulay (Universitas Negeri Islam Sumatera Utara, 2022)
This study was conducted to investigate the effect of Pre-Reading, During Reading, and Post Reading activities to monitor students’ comprehension in reading narrative text. It was conducted in experimental research design. The population of this study was the 8th grade students of MTsS Taman Pendidikan Islam, Medan. The research methodology using in this study was quasi experimental method which consisted of two parallel classes. Both classes were divided into experimental group which was taught by applying Pre-Reading, During Reading, and Post Reading activities, and control group which was taught without applying Pre-Reading, During Reading, and Post Reading activities. The sample was taken Total Sampling. The instrument used to collect the data was multiple choice test. The data were analysed by Mann Whitney U-test. The analysis shows that the significant value of post-test scores in experimental class was 0,013. Which means the significance value is lower than 5% (0,05). The findings indicate that the results of reading comprehension for the students in the experimental class are develop through implementing the Pre-Reading, During Reading, and Post Reading activities. In other words, it can be proved that applying Pre-Reading, During Reading, and Post Reading activities had a significant effect on students’ reading comprehension achievement in narrative text. Keywords: Pre-Reading, During Reading, and Post Reading Activities, Narrative Text